SmFeN magnet and preparation method and application thereof
By using the first and second adhesives in the preparation process of SmFeN magnets, the smooth progress of the injection molding process is ensured, and the adhesive content and density are reduced through the removal and curing steps, the magnetic performance of SmFeN magnets is solved. The poor problem is that SmFeN magnets with high density, high strength, good thermal stability and excellent magnetic properties are achieved.
Patent Information
- Application Number
- CN202411713426.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the content of SmFeN magnets has a high adhesive content during the preparation process, resulting in poor magnetic performance. How to improve the magnetic performance of SmFeN magnets has become an urgent problem to be solved.
The first adhesive and the second adhesive are used to increase the amount of adhesive to ensure the smooth progress of the injection molding process, and then remove the first adhesive, retain the skeleton adhesive, and reduce the residue in the SmFeN magnet. The binder content is cured, and the second binder molecule is migrated, and the pores generated by the removal of the first binder are filled to increase the density of the magnet.
The prepared SmFeN magnet has high magnet density and strong strength; high intrinsic coercive force and strong thermal stability; large residual magnetism and maximum magnetic energy accumulation, and excellent magnetic performance.
Smart Images

Figure BDA0005156321450000131 
Figure BDA0005156321450000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of injection molding, and relates to a magnet and a preparation method and application thereof, and in particular to a SmFeN magnet and a preparation method and application thereof. Background Art
[0002] At present, high-performance magnetic materials are increasingly used in the automotive industry, sensors, aerospace, wind power generation or mobile communications, and the competition for the research and development and industrialization of high-performance rare earth permanent magnet materials is becoming increasingly fierce. NdFeB rare earth permanent magnet material is the permanent magnet material with the best comprehensive performance so far. However, NdFeB permanent magnet has two major drawbacks: first, the poor temperature stability of magnetic properties caused by the low Curie temperature; second, the poor corrosion resistance caused by the different interphase electrode potentials. These two major disadvantages of NdFeB permanent magnet limit its application in the corresponding fields.
[0003] Compared with NdFeB, the saturation magnetization Ms of SmFeN rare earth permanent magnet is 1.54T, which is equivalent to 1.6T of NdFeB; the Curie temperature Tc can reach 470℃, which is much higher than 310℃ of NdFeB; the anisotropy field Ha is 14T, which is also much higher than 8T of NdFeB. At the same time, after years of extensive development and use, NdFeB permanent magnet materials have not only greatly reduced their crustal reserves, but also significantly increased their prices. Furthermore, rare earth mineral resources often coexist in nature. While developing a large amount of Nd resources, a lot of Sm resources are idle, resulting in a serious waste of rare earth resources. The development of SmFeN permanent magnet materials can improve the comprehensive utilization rate of rare earth resources.
[0004] Since SmFeN is easily decomposed at high temperatures exceeding 650°C, the preparation of SmFeN cannot adopt the sintering process to prepare anisotropic sintered magnets like NdFeB. Currently, the more mature preparation process is to prepare anisotropic SmFeN magnets through a bonding process, that is, SmFeN is mixed with polymer materials to form granules, and injection molding is used to prepare injection molded magnets.
[0005] Bonded SmFeN permanent magnet materials have the advantages of excellent molding processability, easy processing into parts with complex shapes and high dimensional accuracy. Bonded SmFeN permanent magnet materials are mainly injection molded, but the traditional injection molding method is used to prepare SmFeN permanent magnets. In order to ensure that the magnets can be smoothly injection molded, a high amount of binder filling is often required, which will lead to a reduction in the overall magnetic item of the magnet, a rapid decrease in magnetic properties, and a waste of the magnetic properties of the material. CN111362681A discloses a high-performance permanent ferrite magnet sintered after injection molding and a preparation method thereof, which mixes the raw materials evenly through three powder mixings, then obtains injection molded permanent ferrite through injection molding, and finally obtains the permanent ferrite magnet through high-temperature sintering. The invention has a high binder content and requires high-temperature sintering and curing, and has high process requirements, and is not suitable for the preparation of SmFeN magnets.
[0006] The existing technology has the defect that the magnetic properties of SmFeN magnets are poor due to the high content of binder in the preparation process. Therefore, how to improve the magnetic properties of SmFeN magnets has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a SmFeN magnet and a preparation method and application thereof, wherein the amount of the binder is increased by using a first binder and a second binder to ensure the smooth progress of the injection molding process, and then the first binder is removed, the skeleton binder is retained, and the binder content remaining in the SmFeN magnet is reduced, and the second binder molecules are migrated by curing to fill the pores generated by the removal of the first binder, thereby improving the density of the magnet. The SmFeN magnet prepared by the present invention has high magnet density and high strength; high intrinsic coercive force and strong thermal stability; large remanence and maximum magnetic energy product, and excellent magnetic properties.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a SmFeN magnet, the preparation method comprising the following steps: after mixing SmFeN powder, a first binder and a second binder, granulation, injection molding, removal of the first binder and curing are performed in sequence to obtain the SmFeN magnet; the first binder and the second binder are different; the first binder comprises alcohol-soluble nylon and / or a wax-based binder; the second binder comprises any one of an olefinic polymer adhesive, a resin binder or a polyamide binder, or a combination of at least two thereof.
[0010] The present invention increases the amount of binder by using a first binder and a second binder to ensure the smooth progress of the injection molding process, then removes the first binder, retains the skeleton binder, reduces the binder content remaining in the SmFeN magnet, and migrates the second binder molecules through curing to fill the pores generated by the removal of the first binder, thereby improving the density of the magnet. The SmFeN magnet prepared by the present invention has high magnet density and high strength; high intrinsic coercive force and strong thermal stability; large remanence and maximum magnetic energy product, and excellent magnetic properties.
[0011] Preferably, the SmFeN powder comprises Sm 2 Fe 17 N X Magnetic powder, wherein 2.8≤x≤3.5, for example, may be 2.8, 2.9, 3, 3.2, 3.4 or 3.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0012] Preferably, the SmFeN powder is anisotropic.
[0013] Preferably, the particle size D50 of the SmFeN powder is 1.5 μm-3 μm, for example, 1.5 μm, 1.8 μm, 2 μm, 2.5 μm, 2.8 μm or 3 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 2 μm-2.5 μm.
[0014] Preferably, the SmFeN powder is surface treated before mixing.
[0015] Preferably, the surface treatment agent comprises a coupling agent diluted with an organic solvent.
[0016] Preferably, the dilution ratio is 1:(4-6), for example, it can be 1:4, 1:4.5, 1:5, 1:5.5, 1:5.8 or 1:6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the coupling agent includes any one of a silane coupling agent, a phosphate coupling agent or a titanate coupling agent, or a combination of at least two of them. Typical but non-limiting combinations include a combination of a silane coupling agent and a phosphate coupling agent, or a combination of a coupling agent, a phosphate coupling agent and a titanate coupling agent.
[0018] Preferably, the silane coupling agent includes any one of KH550, KH560 or KH570 or a combination of at least two thereof. Typical but non-limiting combinations include a combination of silanes KH550 and KH560, or a combination of KH550, KH560 and KH570.
[0019] Preferably, the organic solvent comprises ethanol and / or isopropanol.
[0020] Preferably, the first binder comprises any one of alcohol-soluble nylon, microcrystalline wax or paraffin wax, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of alkane alcohol-soluble nylon and microcrystalline wax, a combination of microcrystalline wax and paraffin wax, or a combination of alcohol-soluble nylon, microcrystalline wax and paraffin wax.
[0021] Preferably, the second binder comprises any one of polypropylene, polyamide, polyethylene or epoxy resin, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of polypropylene and polyamide, or a combination of polyamide, polyethylene and epoxy resin.
[0022] The present invention adopts a first binder and a second binder, wherein the first binder is added to increase the proportion of the binder in the raw material to ensure the smooth progress of the injection molding process, and to enable smooth removal during the removal stage without destroying the entire skeleton structure of the magnet; and the second binder, as a skeleton binder in the magnet, can enhance the mechanical properties of the magnet, and can also fill the pores generated by the removal of the first binder through migration during the curing stage.
[0023] Preferably, the mixed raw materials further include auxiliary agents.
[0024] Preferably, the auxiliary agent includes an antioxidant and a lubricant.
[0025] Preferably, the antioxidant includes antioxidant BASF 1010.
[0026] Preferably, the lubricant includes any one of stearic acid wax, polyamide wax or polypropylene wax, or a combination of at least two of them. Typical but non-limiting combinations include a combination of stearic acid wax and polyamide wax, or a combination of stearic acid wax, polyamide wax and polypropylene wax.
[0027] Preferably, the mixing method comprises ball milling or stirring.
[0028] Preferably, the mixing rotation speed is 500r / min-800r / min, for example, it can be 500r / min, 550r / min, 600r / min, 700r / min, 750r / min or 800r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the mixing environment temperature is 80°C-120°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the mixing time is 30 min-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, based on the total mass of SmFeN powder, the first binder, the second binder, the coupling agent and the additive as 100%, the added amount of the first binder is 6wt%-12wt%, for example, it can be 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or 12wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, based on the total mass of SmFeN powder, the first binder, the second binder, the coupling agent and the additive as 100%, the added amount of the second binder is 2wt%-5wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, based on the total mass of SmFeN powder, the first binder, the second binder, the coupling agent and the auxiliary agent as 100%, the added amount of the coupling agent is 0.3wt%-0.6wt%, for example, it can be 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or 0.6wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, based on the total mass of SmFeN powder, the first binder, the second binder, the coupling agent and the auxiliary agent as 100%, the added amount of the auxiliary agent is 0.4wt%-0.7wt%, for example, it can be 0.4wt%, 0.45wt%, 0.5wt%, 0.6wt%, 0.65wt% or 0.7wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the granulation equipment comprises a twin-screw extruder.
[0036] Preferably, the insulation temperature of the granulation is 180°C-230°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C or 230°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the injection molding mold has an orientation magnetic field.
[0038] Preferably, the mold size for injection molding is diameter (20nm-25mm) × height (8mm-10mm), for example, it can be diameter 20nm × height 8mm, diameter 25nm × height 8mm, diameter 20nm × height 10mm, diameter 25nm × height 10mm, 23nm × height 9mm or 23nm × height 10mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, removing the first binder comprises removing the first binder by soaking in a degreasing solvent.
[0040] Preferably, when the first binder comprises alcohol-soluble nylon, the degreasing solvent comprises an alcohol solvent.
[0041] Preferably, the alcohol solvent includes ethanol and / or isopropanol.
[0042] Preferably, when the first binder comprises microcrystalline wax and / or paraffin wax, the degreasing solvent comprises an ether solvent and / or an oil solvent.
[0043] Preferably, the ether solvent comprises diethyl ether.
[0044] Preferably, the oil solvent includes kerosene and / or gasoline.
[0045] Preferably, the ambient temperature for removing the first binder is 40°C-50°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, after removing the first binder, a defatted material is obtained.
[0047] Preferably, the solidification comprises heating the degreased material to a specific insulation temperature and keeping the temperature for a specific time to obtain the SmFeN magnet.
[0048] Preferably, the curing insulation temperature is 120°C-180°C, for example, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the curing insulation time is 1 h-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] Preferably, the curing heating rate is 5°C / 10min-10°C / 10min, for example, it can be 5°C / 10min, 6°C / 10min, 7°C / 10min, 8°C / 10min, 9°C / 10min or 10°C / 10min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0052] (1) Surface treatment of magnetic powder is performed using a coupling agent diluted with an organic solvent to obtain surface-treated magnetic powder, and the surface-treated magnetic powder, a first binder, a second binder and an auxiliary agent are mixed to obtain a mixture, wherein the mixing environment temperature is 80° C.-120° C., the mixing time is 30 min.-60 min., and the mixing speed is 500 r / min.-800 r / min.
[0053] (2) Extruding the mixed material into granules in a twin-screw extruder to obtain granules, wherein the granulation is carried out at a heat preservation temperature of 180° C. to 230° C.
[0054] (3) The granulated material is placed in an injection molding machine, melted and injected into a mold with a diameter of (20 nm-25 mm) × height of (8 mm-10 mm) and an oriented magnetic field to obtain an injection molding material.
[0055] (4) The injection molding material is placed in a degreasing solvent and heated to 40°C-50°C to remove the first binder to obtain a degreasing material.
[0056] (5) The degreased material is placed in an oven for curing to obtain the SmFeN magnet. The curing insulation temperature is 120° C.-180° C., and the curing insulation time is 1 h-3 h.
[0057] In a second aspect, the present invention provides a SmFeN magnet, which is prepared by the preparation method described in the first aspect.
[0058] In a third aspect, the present invention provides an application of the SmFeN magnet as described in the second aspect, wherein the SmFeN magnet is applied to an automobile motor, a sensor or a water pump rotor.
[0059] Compared with the prior art, the present invention has at least the following beneficial effects:
[0060] (1) The present invention increases the amount of binder by using a first binder and a second binder to ensure the smooth progress of the injection molding process, and then removes the first binder, retains the skeleton binder, reduces the binder content remaining in the SmFeN magnet, and migrates the second binder molecules through curing to fill the pores generated by the removal of the first binder, thereby improving the density of the magnet.
[0061] (2) The SmFeN magnet prepared by the present invention has high magnet density and high strength; high intrinsic coercivity and strong thermal stability; large remanence and maximum magnetic energy product and excellent magnetic properties. DETAILED DESCRIPTION
[0062] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] The alcohol-soluble nylon used in the following examples is ES-1 stable alcohol-soluble nylon from Shanghai Zhenwei, the polyamide 12 is A1709 nylon from Daicel of Japan, the polypropylene is MT45 from Linyi Runcheng, the polyamide wax is SUPER from Arkema of France, and the polypropylene wax is WN-1135 from Arkema of France.
[0064] Example 1
[0065] This embodiment provides a method for preparing a SmFeN magnet, the method comprising the following steps:
[0066] (1) 0.5 parts by mass of KH550 are diluted with 3 parts by mass of ethanol, and magnetic powder is added thereto, the magnetic powder is surface treated to obtain the surface-treated magnetic powder, and the surface-treated magnetic powder, the first binder, the second binder and the auxiliary agent are mixed by ball milling to obtain a mixture, wherein the mixing environment temperature is 100° C., the mixing time is 50 min, and the mixing speed is 600 r / min; the magnetic powder is Sm with a particle size of 2 μm 2 Fe 17 N 3 , the addition amount is 89 parts by mass, the first binder is alcohol-soluble nylon, the addition amount is 7.5 parts by mass, the second binder is polyamide 12, the addition amount is 2.5 parts by mass, the auxiliary agent includes a lubricant and an antioxidant, the lubricant is polyamide wax, the addition amount is 0.2 parts by mass, and the antioxidant is BASF 1010, the addition amount is 0.3 parts by mass;
[0067] (2) extruding the mixed material into granules in a twin-screw extruder to obtain granules, wherein the granulation is carried out at a holding temperature of 180° C.;
[0068] (3) placing the granulated material into an injection molding machine, and melt-injecting it into a mold having a diameter of 25 mm and a height of 10 mm and having an oriented magnetic field to obtain an injection molding material;
[0069] (4) placing the injection molding material in a degreasing solvent and heating it to 45° C. to remove the first binder and obtain a degreasing material; the degreasing solvent is ethanol;
[0070] (5) The degreased material is placed in an oven for curing to obtain the SmFeN magnet. The curing insulation temperature is 160° C., the curing heating rate is 5° C. / 10 min, and the curing insulation time is 1 h.
[0071] Example 2
[0072] This embodiment provides a method for preparing a SmFeN magnet, the method comprising the following steps:
[0073] (1) 0.3 parts by mass of KH560 was diluted with 1.8 parts by mass of ethanol, and magnetic powder was added thereto, the magnetic powder was surface treated to obtain the surface-treated magnetic powder, and the surface-treated magnetic powder, the first binder, the second binder and the auxiliary agent were mixed by ball milling to obtain a mixture, wherein the mixing environment temperature was 80° C., the mixing time was 60 min, and the mixing speed was 500 r / min; the magnetic powder was Sm with a particle size of 1.5 μm. 2 Fe 17 N 2.8 , the addition amount is 91 parts by mass, the first binder is microcrystalline wax, the addition amount is 6 parts by mass; the second binder is polypropylene, the addition amount is 2 parts by mass, the auxiliary agent includes a lubricant and an antioxidant, the lubricant is polypropylene wax, the addition amount is 0.2 parts by mass, and the antioxidant is BASF 1010, the addition amount is 0.5 parts by mass;
[0074] (2) extruding the mixed material into granules in a twin-screw extruder to obtain granules, wherein the granulation temperature is 230° C.;
[0075] (3) placing the granulated material into an injection molding machine, and melt-injecting it into a mold having a diameter of 20 mm and a height of 8 mm and having an oriented magnetic field to obtain an injection molding material;
[0076] (4) placing the injection molding material in a degreasing solvent and heating it to 50° C. to remove the first binder to obtain a degreasing material; the degreasing solvent is ether;
[0077] (5) The degreased material is placed in an oven for curing to obtain the SmFeN magnet. The curing insulation temperature is 120° C., the curing heating rate is 10° C. / 10 min, and the curing insulation time is 1 h.
[0078] Example 3
[0079] This embodiment provides a method for preparing a SmFeN magnet, the method comprising the following steps:
[0080] (1) 0.6 parts by mass of KH570 was diluted with 2.4 parts by mass of ethanol, and magnetic powder was added thereto, the magnetic powder was surface treated to obtain the surface-treated magnetic powder, and the surface-treated magnetic powder, the first binder, the second binder and the auxiliary agent were stirred and mixed to obtain a mixture, wherein the mixing environment temperature was 120° C., the mixing time was 30 min, and the mixing speed was 800 r / min; the magnetic powder was Sm with a particle size of 3 μm. 2 Fe 17 N 3.5 , the addition amount is 82 parts by mass, the first binder is paraffin, the addition amount is 12 parts by mass; the second binder is epoxy resin, the addition amount is 5 parts by mass, the auxiliary agent includes a lubricant and an antioxidant, the lubricant is stearic acid wax, the addition amount is 0.2 parts by mass, and the antioxidant is BASF 1010, the addition amount is 0.2 parts by mass;
[0081] (2) extruding the mixed material in a twin-screw extruder to granulate to obtain granulated material, wherein the granulation is carried out at a holding temperature of 200° C.;
[0082] (3) placing the granulated material into an injection molding machine, and melt-injecting it into a mold having a diameter of 23 mm and a height of 10 mm and having an oriented magnetic field to obtain an injection molding material;
[0083] (4) placing the injection molding material in a degreasing solvent and heating it to 40° C. to remove the first binder and obtain a degreasing material; the degreasing solvent is gasoline;
[0084] (5) The degreased material is placed in an oven for curing to obtain the SmFeN magnet. The curing insulation temperature is 180° C., the curing heating rate is 5° C. / 10 min, and the curing insulation time is 3 h.
[0085] Example 4
[0086] The only difference between this embodiment and embodiment 1 is that, except that the amount of the first binder added in step (1) is 5.5 parts by mass, the rest is the same as embodiment 1.
[0087] Example 5
[0088] The only difference between this embodiment and embodiment 1 is that, except that the amount of the first binder added in step (1) is 12.5 parts by mass, the rest is the same as embodiment 1.
[0089] Example 6
[0090] The only difference between this embodiment and embodiment 1 is that, except that the amount of the second binder added in step (1) is 1.5 parts by mass, the rest is the same as embodiment 1.
[0091] Example 7
[0092] The only difference between this embodiment and embodiment 1 is that, except that the amount of the second binder added in step (1) is 5.5 parts by mass, the rest is the same as embodiment 1.
[0093] Example 8
[0094] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature for curing in step (5) is 110° C., the rest is the same as embodiment 1.
[0095] Example 9
[0096] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of curing in step (5) is 190° C., the rest is the same as embodiment 1.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that, except that 10 parts by mass of alcohol-soluble nylon is used as a binder in step (1), the rest is the same as Example 1.
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 1 is that, except that 10 parts by mass of polyamide 12 is used as a binder in step (1), the rest is the same as Example 1.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 1 is that, except for not performing step (4), the rest is the same as Example 1.
[0103] Comparative Example 4
[0104] The difference between this comparative example and Example 1 is that, except for not performing step (5), the rest is the same as Example 1.
[0105] Comparative Example 5
[0106] This comparative example provides a method for preparing a SmFeN magnet, the preparation method comprising the following steps:
[0107] (1) 0.5 parts by mass of KH550 was diluted with 3 parts by mass of ethanol, and magnetic powder was added thereto, the magnetic powder was surface treated to obtain the surface-treated magnetic powder, and the surface-treated magnetic powder, a binder and an additive were mixed to obtain a mixture, wherein the mixing environment temperature was 100° C. and the mixing time was 50 min; the magnetic powder was Sm with a particle size of 2 μm. 2 Fe 17 N 3 , the addition amount is 89 parts by mass, the binder is polyamide 12, the addition amount is 10 parts by mass, the additives include lubricants and antioxidants, the lubricant is polyamide wax, the addition amount is 0.2 parts by mass, and the antioxidant is BASF 1010, the addition amount is 0.3 parts by mass;
[0108] (2) extruding the mixed material into granules in a twin-screw extruder to obtain granules, wherein the granulation is carried out at a holding temperature of 180° C.;
[0109] (3) The granulated material is placed in an injection molding machine, and melt-injected into a mold with a diameter of 25 mm and a height of 10 mm and an oriented magnetic field to obtain the SmFeN magnet.
[0110] Test Method
[0111] The remanence test method is: using the FE-2100HB-140 permanent magnet material measuring device produced by Hunan Yongyi Technology to test the remanence of the SmFeN magnets prepared in Examples 1 to 9 and Comparative Examples 1 to 5, and record it in Table 1;
[0112] The intrinsic coercivity test method is: using the FE-2100HB-140 permanent magnet material measuring device produced by Hunan Yongyi Technology to test the intrinsic coercivity of the SmFeN magnets prepared in Examples 1 to 9 and Comparative Examples 1 to 5, and record them in Table 1;
[0113] The maximum magnetic energy product is tested by using the FE-2100HB-140 permanent magnet material measuring device produced by Hunan Yongyi Technology to test the maximum magnetic energy product of the SmFeN magnets prepared in Examples 1 to 9 and Comparative Examples 1 to 5, and record the results in Table 1.
[0114] Table 1
[0115]
[0116]
[0117] The test results show that:
[0118] (1) It can be seen from Examples 1 to 9 and Comparative Examples 1 to 5 that the present invention increases the amount of binder by using the first binder and the second binder to ensure the smooth progress of the injection molding process, then removes the first binder, retains the skeleton binder, reduces the binder content remaining in the SmFeN magnet, and migrates the second binder molecules through curing to fill the pores generated by the removal of the first binder, thereby improving the density of the magnet. The SmFeN magnet prepared by the present invention has high magnet density and high strength; high intrinsic coercivity and strong thermal stability; large remanence and maximum magnetic energy product, and excellent magnetic properties.
[0119] (2) It can be seen from Examples 1 and 4 to 7 that the magnetic properties and thermal stability of the SmFeN magnet prepared by further adjusting the amounts of the first binder and the second binder are further improved.
[0120] (3) It can be seen from Example 1 and Example 8-Example 9 that the magnetic properties and thermal stability of the SmFeN magnet prepared by the present invention are further improved by further regulating the curing holding temperature.
[0121] (4) It can be seen from Example 1 and Comparative Examples 1 to Comparative Examples 5 that the present invention further improves the magnetic properties and thermal stability of the SmFeN magnet prepared by selecting two types of binders, the first binder and the second binder, and further removing the first binder and curing.
[0122] In summary, the present invention increases the amount of binder by using the first binder and the second binder to ensure the smooth progress of the injection molding process, then removes the first binder, retains the skeleton binder, reduces the binder content remaining in the SmFeN magnet, and migrates the second binder molecules through curing to fill the pores generated by the removal of the first binder, thereby improving the density of the magnet. The SmFeN magnet prepared by the present invention has high magnet density and high strength; high intrinsic coercive force and strong thermal stability; large remanence and maximum magnetic energy product, and excellent magnetic properties.
[0123] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a SmFeN magnet, characterized in that: The preparation method comprises the following steps: After mixing SmFeN powder, a first binder and a second binder, granulation, injection molding, removal of the first binder and curing are sequentially performed to obtain the SmFeN magnet; The first binder and the second binder are different; The first binder includes alcohol-soluble nylon and / or a wax-based binder; The second adhesive includes any one of olefinic polymer adhesive, resin adhesive or polyamide adhesive, or a combination of at least two of them.
2. The preparation method according to claim 1, characterized in that: The SmFeN powder includes Sm2Fe 17 N X Magnetic powder, where 2.8≤x≤3.5; Preferably, the particle size D50 of the SmFeN powder is 1.5 μm-3 μm, preferably 2 μm-2.5 μm; Preferably, the SmFeN powder is surface treated before mixing.
3. The preparation method according to claim 2, characterized in that: The surface treatment agent includes a coupling agent diluted with an organic solvent; Preferably, the coupling agent includes any one of a silane coupling agent, a phosphate coupling agent or a titanate coupling agent, or a combination of at least two thereof; Preferably, the organic solvent comprises ethanol and / or isopropanol.
4. The preparation method according to any one of claims 1 to 3, characterized in that The first binder includes any one of alcohol-soluble nylon, microcrystalline wax or paraffin wax, or a combination of at least two thereof; Preferably, the second adhesive comprises any one of polypropylene, polyamide, polyethylene or epoxy resin, or a combination of at least two thereof; Preferably, the mixed raw materials further include an auxiliary agent; Preferably, the auxiliary agent includes an antioxidant and a lubricant; Preferably, the mixing environment temperature is 80°C-120°C; Preferably, the mixing time is 30 min-60 min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Based on the total mass of the SmFeN powder, the first binder, the second binder, the coupling agent and the auxiliary agent as 100%, the addition amount of the first binder is 6wt%-12wt%; Preferably, based on the total mass of the SmFeN powder, the first binder, the second binder, the coupling agent and the auxiliary agent being 100%, the added amount of the second binder is 2wt%-5wt%; Preferably, based on the total mass of the SmFeN powder, the first binder, the second binder, the coupling agent and the auxiliary agent being 100%, the added amount of the coupling agent is 0.3wt%-0.6wt%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The granulation holding temperature is 180°C-230°C; Preferably, the injection molding mold has an orientation magnetic field.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The removing of the first binder comprises removing the first binder by soaking with a degreasing solvent; Preferably, when the first binder comprises alcohol-soluble nylon, the degreasing solvent comprises an alcohol solvent; Preferably, when the first binder comprises microcrystalline wax and / or paraffin wax, the degreasing solvent comprises an ether solvent and / or an oil solvent.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The curing insulation temperature is 120°C-180°C; Preferably, the curing insulation time is 1h-3h.
9. A SmFeN magnet, characterized in that: The SmFeN magnet is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the SmFeN magnet according to claim 9, characterized in that: The SmFeN magnet is applied to automobile motors, sensors or water pump rotors.
Citation Information
Patent Citations
High-performance injection-molded post-sintered permanent magnetic ferrite magnet and preparation method thereof
CN111362681A